The ethics gap in the engineering of the future : moral challenges for the technology of tomorrow - Stelios, Spyridon; Theologou, Kostas (Emerald Publishing Limited, 2024)
Advances in computer science, artificial intelligence and data management have made engineering a dynamic and rapidly expanding industry. But have these advances enabled the manifestation of wrongdoing? If so, what can we do to counter this? The Ethics Gap in the Engineering of the Future challenges readers to think about our moral compasses and the multifaceted impact of technology on our everyday lives. Reshaping engineering ethics by considering the 'colonization of lifeworld' by technology and AI-based systems, contributors question human ontology, the cultural status quo and the future of modern civilization. Setting moral reflection at the core of both the engineer's professional practice and the user's personal responsibility, the chapters address the moral implications of biotechnology and artificial intelligence, the ethical challenges of regulation and digital governance and the ethics of space exploration. Offering visionary case studies, authors explore issues such as privacy, regulation, inequality, social exclusion/inclusion, human judgment, decision-making, freedom, legitimacy, responsibility, safety and other ethical issues in engineering. Challenging philosophers, academics, engineers, researchers, educators and scholars to prioritise these moral quandaries before it's too late, this is an insightful look into engineering ethics and the technology of tomorrow.